2023
DOI: 10.1088/1361-648x/acba73
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Pt/Co/AlO x heterostructures to enhance the Dzyaloshinskii–Moriya interaction

Abstract: The study of interfacial Dzyaloshinskii-Moria interaction (DMI) in perpendicularly magnetized structurally asymmetric heavy metal /ferromagnet multilayer systems is of high importance due to the formation of chiral magnetic textures in the presence of DMI. Here, we report the impact of cobalt oxidation at the Co/AlOx interface in Pt/Co/AlOx trilayer structures on the DMI by varying the post-growth annealing time, Al thickness and substrate. To quantify DMI we employed magneto-optical imaging of the asymmetric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
0
0
Order By: Relevance
“…However, the control of DMI has always been challenging and has only been experimentally confirmed in recent years . Studies have demonstrated that the DMI strength in hybrid ferroelectric-ferromagnetic systems can be effectively manipulated by external stimuli such as electric fields and strain. , These factors can bring about significant alterations to the DMI of the system. For instance, Srivastava et al achieved a 130% variation of DMI (about 0.1 ± 0.04 mJ/m 2 ) with an electric field in Ta/FeCoB/TaO x trilayer through the Brillouin Light Spectroscopy (BLS) method .…”
mentioning
confidence: 99%
“…However, the control of DMI has always been challenging and has only been experimentally confirmed in recent years . Studies have demonstrated that the DMI strength in hybrid ferroelectric-ferromagnetic systems can be effectively manipulated by external stimuli such as electric fields and strain. , These factors can bring about significant alterations to the DMI of the system. For instance, Srivastava et al achieved a 130% variation of DMI (about 0.1 ± 0.04 mJ/m 2 ) with an electric field in Ta/FeCoB/TaO x trilayer through the Brillouin Light Spectroscopy (BLS) method .…”
mentioning
confidence: 99%